Share price reaction due to the disposal of equity interest announcements / Susana Narawi - Narawi, Susana (2004)
Disposal of equity interest is part of the immediate publicly announcements require by the KLSE Listing Requirement. The scope of study involves all the disposal of equity interest announcements made by the public listed companies on Bursa Malaysia throughout year 2003. Two commonly event studies model, which are MAR model and market model were employed in the process to identify the average abnormal returns, cumulative average abnormal returns and finally to determine the trend of the cumulative returns.